2007
DOI: 10.1007/s11103-007-9146-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutated acetolactate synthase gene conferring specific resistance to pyrimidinyl carboxy herbicides in rice

Abstract: Acetolactate synthase (ALS) is the first common enzyme in the biosynthetic pathway of branched-chain amino acids. Mutations of specific amino acids in ALS have been known to confer resistance to ALS-inhibiting herbicides such as sulfonylureas and pyrimidinyl carboxy (PC) herbicides. However, mutations conferring exclusive resistance to PC have not yet been reported to date. We selected PC resistant rice calli, which were derived from anther culture, using one of the PCs, bispyribac-sodium (BS), as a selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…A BS-insensitive mutant ALS gene has been used widely as a positive marker to obtain transformed cells and plants under BS selection. For example, a combination of a mutated rice ALS gene and BS selection has been applied in rice (Osakabe et al, 2005;Okuzaki et al, 2007;Wakasa et al, 2007;Taniguchi et al, 2010), wheat (Ogawa et al, 2008), tall fescue (Festuca arundinacea; Sato et al, 2013), Arabidopsis (Kawai et al, 2010), and soybean (Glycine max; Tougou et al, 2009). Like the mutated ALS gene, the CYP81A6 gene has also been reported as a selection marker with BSM in Arabidopsis, cotton (Gossypium hirsutum), and tobacco plants (Ke et al, 2012;Liu et al, 2012).…”
Section: Application Of the Cyp72a31 Gene To A Broad Array Of Technolmentioning
confidence: 99%
“…A BS-insensitive mutant ALS gene has been used widely as a positive marker to obtain transformed cells and plants under BS selection. For example, a combination of a mutated rice ALS gene and BS selection has been applied in rice (Osakabe et al, 2005;Okuzaki et al, 2007;Wakasa et al, 2007;Taniguchi et al, 2010), wheat (Ogawa et al, 2008), tall fescue (Festuca arundinacea; Sato et al, 2013), Arabidopsis (Kawai et al, 2010), and soybean (Glycine max; Tougou et al, 2009). Like the mutated ALS gene, the CYP81A6 gene has also been reported as a selection marker with BSM in Arabidopsis, cotton (Gossypium hirsutum), and tobacco plants (Ke et al, 2012;Liu et al, 2012).…”
Section: Application Of the Cyp72a31 Gene To A Broad Array Of Technolmentioning
confidence: 99%
“…Mutated ALS genes derived from Arabidopsis have been reported to be useful as selectable markers in various plants, such as tobacco (Gabard et al, 1989), rice (Li et al, 1992), potato (Anderson et al, 2003), oilseed mustard (Brassica juncea) (Ray et al, 2004) and maize (Zhang et al 2005). Mutated OsALS genes have been demonstrated to be useful as selectable markers in rice (Osakabe et al, 2005;Okuzaki et al, 2007). Using these mutated OsALS genes, transgenic plants have been produced in various plants such as rice (Osakabe et al, 2005;Okuzaki et al, 2007), soybeans (Tougou et al, 2009), tall fescue (in preparation) and wheat (Triticum aestivum L.) (Ogawa et al, 2008).…”
Section: The Use Of Mutated Als Genes As Selective Markersmentioning
confidence: 99%
“…Mutated OsALS genes have been demonstrated to be useful as selectable markers in rice (Osakabe et al, 2005;Okuzaki et al, 2007). Using these mutated OsALS genes, transgenic plants have been produced in various plants such as rice (Osakabe et al, 2005;Okuzaki et al, 2007), soybeans (Tougou et al, 2009), tall fescue (in preparation) and wheat (Triticum aestivum L.) (Ogawa et al, 2008). Some studies have suggested that homology-dependent gene silencing is associated with the presence of either multiple copies of homologous transgenes and promoters (Matzke & Matzke, 1995) or a transgene and a homologous endogenous gene (Meyer, 1995).…”
Section: The Use Of Mutated Als Genes As Selective Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…An amino acid substitution at a particular position in ALS has been shown to confer resistance to herbicides such as sulfonylureas and imidazolinones and to pyrimidinyl carboxy herbicides. Mutant forms of the ALS gene have been reported to be useful as a selectable marker in many plant species, such as potato (Andersson et al 2003), oilseed mustard (Ray et al 2004), rice (Okuzaki et al 2007;Osakabe et al 2005), maize (Zhang et al 2005), cotton (Rawat et al 2008), wheat (Ogawa et al 2008), and soybean (Tougou et al 2009). The use of an ALS gene derived from the host crop itself would be expected to result in a more publicly acceptable genetically modified (GM) crop compared with the use of a conventional antibiotic selectable marker.…”
mentioning
confidence: 99%